The Important of Civic Engagement in the Indonesian Nasional Curriculum: Literature Review - Maharani, Okvi; Sarwi, Sarwi; Widiyatmoko, Arif (Proceedings of International Conference on Science, Education, and Technology, 2025)
This study aims to examine the importance of civic engagement in the Indonesian national curriculum through a literature review approach. Civic engagement is a key element in building students' national identity, character, and social competence. Integrating civic engagement into the curriculum is essential for preparing young generations to become active, critical, and responsible citizens, both nationally and globally. The literature review method used in this study involves identifying, analyzing, and synthesizing scientific articles, research reports, and policy documents from national and international sources published between 2015 and 2025. The findings reveal that although civic engagement has been partially incorporated into the curriculum, it remains largely confined to specific subjects and extracurricular activities without cross-disciplinary integration. Several challenges hinder the optimal implementation of civic engagement, including insufficient teacher training, an overemphasis on cognitive assessments, infrastructure disparities, lack of clear policy guidelines, and limited community involvement. Addressing these issues requires systematic efforts such as enhancing active learning methods, balancing cognitive and experiential assessments, providing equitable infrastructure, and fostering stronger collaboration between schools and communities. This study underscores the urgent need for comprehensive and structured integration of civic engagement across the curriculum to develop a generation capable of upholding democratic values and contributing positively to a diverse, interconnected world.